2016
DOI: 10.1088/0957-4484/27/37/375401
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of hematite nanorod photoanodes with a phosphorus overlayer for enhanced photoelectrochemical water oxidation

Abstract: Hematite (i.e., α-Fe2O3) nanorod photoanodes passivated with a phosphorus overlayer have been fabricated by decomposing sodium hypophosphite (NaH2PO2) at a low temperature over the hematite nanorod surface. Extensive scanning electron microscopy, transmission electron microscopy, x-ray diffractometry and UV-vis spectroscopy characterizations confirm that conformal deposition of an amorphous phosphorus overlayer does not change the crystal structure, morphology, and optical absorption properties of hematite pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…As mentioned, the passivation of the α‐Fe 2 O 3 surface by depositing a thin overlayer of metal oxides, metal hydroxides, graphene, g‐C 3 N 4 , etc ., has a great impact on the charge separation as well as charge transfer enhancement across the solid‐liquid interface. There are different theories to explain the role of the passivation layer in improving the PEC water oxidation performance , ,. Yang et al .…”
Section: General Strategies To Improve the Photoelectrochemical Perfomentioning
confidence: 99%
“…As mentioned, the passivation of the α‐Fe 2 O 3 surface by depositing a thin overlayer of metal oxides, metal hydroxides, graphene, g‐C 3 N 4 , etc ., has a great impact on the charge separation as well as charge transfer enhancement across the solid‐liquid interface. There are different theories to explain the role of the passivation layer in improving the PEC water oxidation performance , ,. Yang et al .…”
Section: General Strategies To Improve the Photoelectrochemical Perfomentioning
confidence: 99%
“…[13][14][15] However, PEC performance of a-Fe 2 O 3 has been hindered by intrinsic material limitations resulting in al ate onsetp otential [0.9-1.1 Vv s. the reversible hydrogen electrode (V RHE )], [16] short hole-diffusion length (L h % 2-4 nm), [17] poor OER performance, [18] and high charge-recombination rate. [3,21] For instance,v arious layers containing TiO 2 , [22] Al 2 O 3 , [23] Ti-doped SiO x , [9] Ga 2 O 3 , [24] and amorphous phosphorus [25] enhanced PEC performance by passivating the surface states of a-Fe 2 O 3 . Various strategies, including the use of passivation layers and/or co-catalysts have shown to reduce the onset potential of a-Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies, including the use of passivation layers and/or co-catalysts have shown to reduce the onset potential of a-Fe 2 O 3 . [3,21] For instance,v arious layers containing TiO 2 , [22] Al 2 O 3 , [23] Ti-doped SiO x , [9] Ga 2 O 3 , [24] and amorphous phosphorus [25] enhanced PEC performance by passivating the surface states of a-Fe 2 O 3 . Furthermore, diverse co-catalysts including FeOOH, [26] IrO 2 , [14] Ni(OH) 2 , [27,28] and CoÀPi [29,30] (Co-Pi = Cobalt-phosphate) have been widely studied for decreasing onset potentialb yi ncreasing the OER performance of a-Fe 2 O 3 .Overall, the picture resulting from these studies suggest that ac omplementary contributionf rom surface-state passivation and enhanced surface catalysis is responsible for the observedg ain in onset potential for functionalized a-Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…TA spectroscopy shows that the enhanced PEC responses of heterostructured photoanodes are mainly due to an enhanced charge separation. Additionally, non-metal surface passivation of hematite using e.g., phosphorus [57], or bromide [58] were previously presented. It was shown that amorphous phosphorus is able to passivate surface states of a hematite nanorod photoanode and to suppress electron-hole recombination, significantly enhancing the photocurrent for water oxidation [57].…”
Section: Surface Passivationmentioning
confidence: 99%
“…They found that partial HCl wet-etching Additionally, non-metal surface passivation of hematite using e.g., phosphorus [57], or bromide [58] were previously presented. It was shown that amorphous phosphorus is able to passivate surface states of a hematite nanorod photoanode and to suppress electron-hole recombination, significantly enhancing the photocurrent for water oxidation [57]. It is proposed that cetyltrimethylammonium bromide (CTAB) modification of the hematite surface leads to an increase of carrier density favoring the transport of the charge carriers [58].…”
Section: Surface Chemical Etchingmentioning
confidence: 99%